Phosphorylation of PI3K/Akt at Thr308, but not phosphorylation of MAPK kinase, mediates lithium-induced neuroprotection against cerebral ischemia in mice - Ateş, Nilay; Çağlayan, Aysun; Balçıkanlı, Zeynep; Sertel, Elif; Beker, Mustafa Çağlar; Dilsiz, Pelin; Çağlayan, Ahmet Burak; Çelik, Süleyman; Daşdelen, Muhammed Furkan; Çağlayan, Berrak; Yiğitbaşı, Türkan; Özbek, Hanefi; et al. (Academic Press Inc., 2022)
Lithium, in addition to its effect on acute and long-term bipolar disorder, is involved in neuroprotection after ischemic stroke. Yet, its mechanism of action is still poorly understood, which was only limited to its modulatory effect on GSK pathway. Therefore, we initially analyzed the dose-dependent effects of lithium on neurological deficits, infarct volume, brain edema and blood-brain barrier integrity, along with neuronal injury and survival in mice subjected to focal cerebral ischemia. Thereafter, we investigated the involvement of the PI3K/Akt and MEK signal transduction pathways and their components. Our observations revealed that 2 mmol/kg lithium significantly improved post-ischemic brain tissue survival. Although, 2 mmol/kg lithium had no negative effect on brain microcirculation, 5 and 20 mmol/kg lithium reduced brain perfusion. Furthermore, supratherapeutic dose of lithium in 20 mmol/kg lead to animal death. In addition, improvement of brain perfusion with L-arginine, did not change the effect of 5 mmol/kg lithium on brain injury. Additionally, post-stroke blood-brain barrier leakage, hemodynamic impairment and apoptosis have been reversed by lithium treatment. Interestingly, lithium-induced neuroprotection was associated with increased phosphorylation of Akt at Thr308 and suppressed GSK-3? phosphorylation at Ser9 residue. Lithium upregulated Erk-2 and downregulated JNK-2 phosphorylation. To distinguish whether neuroprotective effects of lithium are modulated by PI3K/Akt or MEK, we sequentially blocked these pathways and demonstrated that the neuroprotective activity of lithium persisted during MEK/ERK inhibition, whereas PI3K/Akt inhibition abolished neuroprotection. Collectively, we demonstrated lithium exerts its post-stroke neuroprotective activity via the PI3K/Akt pathway, specifically via Akt phosphorylation at Thr308, but not via MEK/ERK.
Keywords: Focal Cerebral Ischemia; Lithium; Neuroprotection; PI3K Inhibition; PI3K/Akt Signaling Pathway